Alterações na produtividade e composição nutricional de uma pastagem após segundo ano de aplicação de diferentes doses de cama de frango - Quintao Lana, Regina Maria; de Assis, Daniel Ferreira; Silva, Adriane de Andrade [UNESP]; Quintao Lana, Angela Maria; Guimaraes, Ednaldo Carvalho; Borges, Elias Nascentes (Universidade Federal de Uberlândia (UFU), 2010)
The objective was to evaluate the potential use of poultry litter, compared to mineral fertilization, productivity, features bromatologic and absorption of nutrients from a pasture of Brachiaria decumbens. The experimental area was installed in oxisoil in Uberlandia-MG. The design was randomized blocks with four replicates and the treatments used: control (without application of organic or mineral source), mineral fertilizer (60, 75 and 100 kg ha(-1), P K, respectively); organic fertilization with poultry litter at rates of 3,125, 6,250, 9,375 and 12,500 kg ha(-1). There were two cuts of the aerial part of Brachiaria decumbens, both at 60 days after treatment. We evaluated the yield of DM and the levels of CP, NDF, ADF, lignin, macro and micronutrients in shoots of grass. The results showed that application of poultry litter increased the productivity of DM and the levels of CP, N, P, K and Zn in Brachiaria decumbens. The poultry litter can be used as supplementary source of nutrients, the mineral fertilizer. The use of poultry litter not increased over the levels of S, Ca and Mg in Brachiaria decumbens.

Objetivou-se avaliar a capacidade de liberação de nutrientes da cama de frango e fontes minerais e seu efeito na produtividade, características bromatológicas e absorção de nutrientes de uma pastagem de Brachiaria decumbens. Conduziu-se a área experimental sob Latossolo vermelho distrófico típico, em Uberlândia-MG. O delineamento foi de blocos casualizados com 4 repetições. Aplicou-se os tratamentos controle (sem aplicação de fonte orgânica ou mineral); adubação mineral com equivalente a 60; 75 e 100 kg ha-1 de N:P:K; e as doses de cama de frango equivalentes a 3.125; 6.250; 9.375; 12. 500 kg ha-1. Realizaram-se duas coletas foliares com 60 dias de estágio de maturação da parte aérea da Brachiaria decumbens e avaliou-se a produtividade de MS, teores de PB, FDN, FDA, Lignina e macro e micronutrientes foliares. Após as determinações observou-se que a aplicação de cama de frango resultou em aumento da matéria seca, proteína bruta, N, P e K da Brachiaria decumbens. A cama de frango pode ser usada como complementar a adubação mineral. A adubação orgânica não causou aumento sobre os teores de S, Ca e Mg na matéria seca da Brachiaria decumbens
Changes in productivity and nutritional composition of a pasture after the second year of implementation of different doses of poultry litter
Keywords: Farms residues; Recycling of nutrients; Organic fertilizer